Liquidity, profitability, tax rate and bankruptcy risk in Colombian SMEs - Andrade-Valbuena, Nelson A.; Moscoso Duran, Fabio; Salcedo-Perez, Carlos (Estudios de Administración, 2017)
This article looks for statistical evidence for the correlation between liquidity, profitability, tax rates and bankruptcy risk for the period 2011 - 2016 among Small and Medium Enterprises in Bogotá (Colombia). To do so, the authors conducted a quantitative, longitudinal research using the Altman Z’’ Score index. Data from 2,084 enterprises belonging to 19 industries was collected. The relations between the variables were analyzed applying the Pearson correlation coefficient. A significant positive correlation between the risk of failure and low levels of liquidity was evidenced in several industries. The results for the relation between the risk of bankruptcy and profitability were not conclusive, nor were they significant. Not enough statistical evidence that related rates of return or tax rates to risk of failure was found.